2007
DOI: 10.1111/j.1365-2885.2007.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dirlotapide, a microsomal triglyceride transfer protein inhibitor, on the digestibility of a dry expanded diet in adult dogs

Abstract: The objectives of this study were to evaluate the effects of dirlotapide, a microsomal triglyceride transfer protein inhibitor, on apparent nutrient digestibility of an expanded dry dog food, on defecation frequency and fecal consistency. Eighteen beagles were randomized to either placebo (n = 6) or dirlotapide (n = 12). Testing was divided into a 21-day adaptation phase (days -21 to -1) and a 35-day treatment (digestibility testing) phase (days 0-35). During the treatment phase, dogs were administered oral di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…, 2004). Conversely, the increase in fecal fat produced by MTP inhibition does not change fecal consistency or defecation frequency presumably because the dietary fat is normally digested (Kirk et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…, 2004). Conversely, the increase in fecal fat produced by MTP inhibition does not change fecal consistency or defecation frequency presumably because the dietary fat is normally digested (Kirk et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In pharmacodynamic investigations, it has been found that at low doses (up to 0.5 mg/kg dirlotapide daily) fecal fat increased from about 5% before treatment to as much as 30% (Wren et al. , 2007b); however, no change in fecal volume or consistency was found at 0.3 mg/kg/day (Kirk et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the relative selectivity of the compound, as dirlotapide has much greater effects on MTP present in enterocytes than in hepatocytes (M. A. Hickman personal communication). Based on fat digestibility studies in obese beagles, fat absorption is reduced by dirlotapide from around 90% to approximately 84% (Kirk et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A direct mechanism of action of dirlotapide is the inhibition of fat absorption. This inhibition is only partial and plays a minor contributing role in the weight loss observed following treatment with dirlotapide (Kirk et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%